Our wild familiars : how animals are adapting to cities and reshaping the natural world - Werb, Dan (Crown, 2026)
"A dazzling journey into the hidden lives of synanthropes, the wild animals who've found ingenious ways to survive and thrive in human communities-from award-winning writer and epidemiologist Dan Werb Synanthropes have always been an immutable part of the tapestry of our lives. They are the reason we hear birdsong in the morning and skittering throughout the day, and why we take such pains to fix lids to our garbage cans. But they are so much more than that, too: epidemic vectors, churners of soil, ecosystem evolvers, spiritual lodestars, and, sometimes, sharp-toothed marauders making their way through our most intimate spaces with cruel intent. But beyond their quotidian impact on our lives, synanthropes have a critical part to play in how our communities are shaped and how sustainably they will function. These creatures are ambassadors from nature, arbiters of our planet's future, and a key influence on our species' ongoing evolution; and something essential has shifted with them. We are entering a fraught era of environmental disruption, habitat destruction, and human population expansion that is ravaging formerly wild and untouched lands. And with that, we are coming face to face with an entirely new class of synanthropes that are bringing chaos and danger-as well as opportunity-to our doorstep. These creatures, so long dismissed, are forcing us to reckon with them. Through vivid storytelling, Our Wild Familiars brings to spectacular life the world's most successful synanthropes, from bats, raccoons, and crows, to some of its weirdest, including the Giant Pacific Octopus. Acting as a guide to the curious, Werb reveals how the cracks in our millennia-long efforts to shield ourselves against the outside world might just lead us to a new and necessary harmony with nature-or to an ever more savage future"--